(untitled) (Research, Society and Development, 2022)
This work aimed to present the profile of undergraduate and graduate students in physical education working in the areas of education and health. The methodology used for this article was a qualitative, academic and descriptive approach, with the aim of discussing the possible role of future physical education professionals in the areas of education and health. Result: a total of 78 volunteers participated in the study who answered a google forms questionnaire with open and closed questions and variation in the likert scale. It is concluded that physical education students are mostly young males and despite the large number of bachelors, the area of school physical education still seems to be very coveted. On the other hand, there is also an increase in the public that thinks of providing care and prescribing physical activities with a view to the health of children and young people in specialized care for people with disabilities and special needs.